Mixed effects of elevated pCO2 on fertilisation, larval and juvenile development and adult responses in the mobile subtidal scallop Mimachlamys asperrima (Lamarck, 1819) - Scanes, E; Parker, L M; O'Connor, W A; Ross, P M (PLoS ONE, 2014)
Ocean acidification is predicted to have severe consequences for calcifying marine organisms especially molluscs. Recent studies, however, have found that molluscs in marine environments with naturally elevated or fluctuating CO 2 or with an active, high metabolic rate lifestyle may have a capacity to acclimate and be resilient to exposures of elevated environmental pCO2. The aim of this study was to determine the effects of near future concentrations of elevated pCO2 on the larval and adult stages of the mobile doughboy scallop, Mimachlamys asperrima from a subtidal and stable physiochemical environment. It was found that fertilisation and the shell length of early larval stages of M. asperrima decreased as pCO2 increased, however, there were less pronounced effects of elevated pCO 2 on the shell length of later larval stages, with high pCO 2 enhancing growth in some instances. Byssal attachment and condition index of adult M. asperrima decreased with elevated pCO2, while in contrast there was no effect on standard metabolic rate or pHe. The responses of larval and adult M. asperrima to elevated pCO2 measured in this study were more moderate than responses previously reported for intertidal oysters and mussels. Even this more moderate set of responses are still likely to reduce the abundance of M. asperrima and potentially other scallop species in the world'fcs oceans at predicted future pCO2 levels. © 2014 Scanes et al.